Should I Prescribe This Drug? - Ball, William L. (1973)
The physician constantly receives new information about pharmaceutical products from a variety of sources. This article attempts to sort out some of this information as it applies to the practicing physician. Regulations for drug testing, reliability standards for clinical trials, standards for establishing therapeutic equivalency and bioavailability mechanisms are described.